MEDIA PEMBELAJARAN BERBAHAN LOOSE PART DALAM PEMBELAJARAN EKSAK DI MI KEDUNGWULUH LOR - Sri Muryaningsih (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
Media is a tool that is used to convey informatiabson from the sender of the message to the recipient of the message. Learning media is defined as a tool used by teachers to convey learning material to students, and a means of communication between students and students. There are problems such as the use of learning media at MI Muhammadiyah Kedungwuluh Lor is not optimal. This activity seeks to provide assistance in creating and using learning media, especially in exact subjects so that student learning outcomes are getting better.